KAJIAN YURIDIS ALIH TEKNOLOGI DALAM PERUSAHAAN MULTINASIONAL - Bisma Prayogi, Kadek; Dharmakusuma, A. A. Gde Agung; Putrawan, Suatra (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013, 2013)
The role of multinational enterprises (PMN) in technology transfer thatcan be mentioned such as : as a parent company that can be used for media, theform of information exchange, technology among countries within internationalsociety which is then beneficial and useful for Indonesia; as the place to capitalinvestment in order to have benefit for Indonesia; and as the place to implementnew technology in order to be used more efficiently and effectively for Indonesia,in addition to improve international economic trade.The regulation of technology transfer toward multinational enterprises(PMN) still focuses on Act No. 25 of 2007 concerning capital investment,especially Article 2 Point 1, in addition Indonesia has also referred to nationallegal regulation in economic /trade affairs based on GATT and WTO that havebeen ratified through RI Act No. 7 of 1994, included adaptation to regulation ofIntellectual Property Rights (HKI) available in TRIPs, like RI Act No. 14 of 2001concerning patent, RI Act No. 15 of 2001 about trade mark, and RI Act No. 19 of2002 concerning copy rights and others included object from IntellectualProperty Rights (HKI).
Keywords: Technology, Transfers, Multinational, Enterprises